DE LA REFLEXION PHILOSOPHIQUE SUR LE MODELE DU DEVELOPPEMENT POUR L’AFRIQUE - SELENGE Junior, TUNGATU (IJRDO-Journal of Applied Science, 2021)
My greater anxiety is the one of unsetting, by a critical thought, the philosopher’s role in the questionable mode of life in the development in Africa, from phenomenological perspective. At the end of my researches, i whrite that the true development must be entire, that is to say, the one wich aims at the development of any man and of the whole man. So, to reach this ideal, the philosopher’s role must be the one of thinking, creating concepts, clearing, staying up, awaking conscience. He must be the philosopher who predicts, foresees, encourages and teaches popular mass what he must think and act for reaching good fortune expressed in the best being of persons.